Case Report: The molecular fingerprint and the clinical implication of an exceptional response to neoadjuvant therapy in a metastatic cardia adenocarcinoma - Lorenzon, Laura; Campisi, Andrea; Di Paolo, Alessandra; Giuliante, Felice; Buttitta, Fiamma; D’Ugo, Domenico (Frontiers in Surgery, 2024)
Background Globally, gastric cancer holds the fifth position in terms of prevalence among malignant tumors and is the fourth leading cause of cancer-related mortality. Particular attention should be paid to cardia adenocarcinoma (CA) due to its increasing incidence and poor prognosis. Diagnosis of CA frequently occurs in advanced stages because of its late symptoms. In such cases, neoadjuvant chemotherapy is the primary treatment option. The response to chemotherapy depends on multiple variables including the tumor's molecular profile, the patient's performance status, and the feasibility of using targeted therapy. Patients exhibiting an exceptional response, defined as a complete response to medical therapy lasting more than 1 year, or a partial response or stable disease lasting more than 2 years, are rarely described. This case report presents one of the longest-lasting exceptional responses to chemotherapy in metastatic cardia adenocarcinoma and discusses its clinical implications. Case presentation A 49-year-old male patient presented with cardia adenocarcinoma (human epidermal growth factor receptor 2 negative, mismatch repair proficient) and liver metastases. Molecular profiling identified a pathogenic mutation in the TP53 gene (R123W; Arg123Trp) as the sole alteration found. Five months after initiating the neoadjuvant chemotherapy with fluorouracil–leucovorin–oxaliplatin–docetaxel, the patient achieved a complete clinical response. The molecular profile was compared with others previously documented in an international data portal, revealing a similar pattern. At 4 years and 3 months from diagnosis, the exceptional response was still confirmed. The patient underwent a cumulative number of 33 cycles of chemotherapy, leading to chemotherapy-induced liver damage. Conclusions Exceptional responses to neoadjuvant chemotherapy in cardia adenocarcinomas are rarely reported. The documentation of exceptional responses to cancer therapies should be included in large data repositories to explore the molecular fingerprint of these tumors. In such cases, the clinical implications of long-term chemotherapy should always be taken into account.